Konflik Peran terhadap Komitmen Organisasi melalui Kepuasan Kerja Sebagai Variabel Intervening - Dwi Lestari; Ralina Transistari (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2020)
This study aims to “analyze the effect of role conflict on organizational commitment, role conflict on job satisfaction, the effect of job satisfaction on organizational commitment, and to analyze the effect of role conflict on organizational commitment through job satisfaction as an intervening variable for employees of STIM YKPN Yogyakarta.” The independent variable in this study is role conflict, the dependent variable is organizational commitment and the intervening variable is job satisfaction. This research uses quantitative methods with linear regression data analysis, path analysis, and Sobel test.” The sampling technique uses non-probability with a saturated sampling method. The sample studied was 38 permanent employees of STIM YKPN Yogyakarta consisting of 18 administrative employees and 20 maid service employees. The results obtained from this study are role conflict does not affect employee organizational commitment, but role conflict affects job satisfaction, and job satisfaction affects organizational commitment. This study also found that “role conflict affects organizational commitment through job satisfaction as an intervening variable